Key Players in Economic Development - Ashani Amarasinghe; Roland Hodler; Paul A. Raschky; Yves Zenou (Institute of Labor Economics (IZA), 2020)
This paper analyzes the role of networks in the spatial diffusion of local economic shocks in Africa. We show that road and ethnic connectivity are particularly important factors for diffusing economic spillovers over longer distances. We then determine the key players, i.e., which districts are key in propagating local economic shocks across Africa. Using these results, we conduct counterfactual policy exercises to evaluate the potential gains from policies that increase economic activity in specific districts or improve road connectivity between districts.
Keywords: O13; O55; R12; 330; transportation; natural resources; key player centrality; spatial spillovers; networks; Africa